2020
DOI: 10.1097/iae.0000000000002368
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and Visual Outcomes of Inverted Internal Limiting Membrane Flap Technique Versus Internal Limiting Membrane Peeling in Myopic Macular Hole Without Retinal Detachment

Abstract: Purpose: To compare the results of vitrectomy with internal limiting membrane (ILM) peeling and inverted ILM flap for treating myopic macular hole without retinal detachment. Methods: Twenty-eight eyes of 28 patients undergoing vitrectomy with either ILM peeling (n = 16) or inverted ILM flap technique (n = 12) were included. Outcomes were myopic macular hole closure by optical coherence tomography and visual acuity at 6 months and at the end of follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
20
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 38 publications
7
20
2
Order By: Relevance
“…Other authors have reported closure rates of 83% to 100% [11]. With regard to the BCVA, the percentage of patients with a vision improvement after ILM peeling ranges from 41% to 83% [11, 12, 13, 14]. In the present study, BCVA increased in 76% of idiopathic MH and 71% of myopic MH cases (ILM peeling group), with no statistical differences.…”
Section: Discussionsupporting
confidence: 45%
“…Other authors have reported closure rates of 83% to 100% [11]. With regard to the BCVA, the percentage of patients with a vision improvement after ILM peeling ranges from 41% to 83% [11, 12, 13, 14]. In the present study, BCVA increased in 76% of idiopathic MH and 71% of myopic MH cases (ILM peeling group), with no statistical differences.…”
Section: Discussionsupporting
confidence: 45%
“…High myopia over −6.0 diopters can be complicated with a secondary MH [ Figure 2]. [36,37] The pathophysiology is not fully understood. It has been suggested that the pathologic growth of the eyeball in myopic eyes may lead to posterior staphyloma, manifesting as a posterior scleral protrusion.…”
Section: Myopic Mhs (Mmhs)mentioning
confidence: 99%
“…[41] The growing anteroposterior axial length together with the VMT can lead to foveoschisis and the formation of a FMTH. [37,41,42] Retinal detachment is a rare complication of idiopathic MH, but it is relatively more frequent in cases of MMHs. [39,43] The reported incidence of foveoschisis in high myopia is 9-34%, and approximately 50% of patients with foveoschisis will subsequently develop either a MH or retinal detachment within 2 years.…”
Section: Myopic Mhs (Mmhs)mentioning
confidence: 99%
See 2 more Smart Citations